UPAYA MENINGKATKAN KETERAMPILAN BERTANYA DAN PRESTASI BELAJAR SISWA MELALUI MODEL DISCOVERY LEARNING PADA TEMA 7 PERISTIWA DALAM KEHIDUPAN DI KELAS VB SD NEGERI 1 KEDUNGBANTENG - Alfina Nurlitasari; Badarudin Badarudin; Karma Iswasta Eka (Universitas PGRI Semarang, 2019)
This research is motivated by the low level of questioning skills and student achievement. The purpose of this study is to see the improvement of questioning skills and student achievement by applying the Discovery Learning model. The type of research used is Classroom Action Research (CAR). The subjects in this study were 26th grade students of VB SD Negeri 1 Kedungbanteng, consisting of 13 male students and 13 female students. The data collection tool uses learning evaluation tests, observation sheets, questioning skills, observation sheets, activities of teachers and students. The results of the study show that learning using the Discovery Learning model can improve the skill of asking students who are in the criteria of skill and learning achievement that is in very good criteria.Keywords: Questioning Skills, Learning Achievement, Discovery Learning Model